Assesing Economic Policies in Zimbabwe: The Growth with equity policy 1981 - Mutenga, Marian; Vyas-Doorgapersad, Shikha (Journal of Economic Development, Environment and People, 2022)
There are various economic policies implemented in Zimbabwe to improve the socio-economic standards of the nation. The current article only focuses on the Growth with Equity Policy. The article assesses that the pre-independence policies in Zimbabwe were biased towards enrichment of the minority colonial regime. In Zimbabwe when it gained independence, a number of economic policies were put into place with an emphasis on equity-based socioeconomic growth. In order to correct historical inequities and promote social justice and inclusion for all Zimbabweans, it was also intended to offer parity and balance. Nevertheless, despite the Zimbabwean government's implementation of several economic measures since 1980, the country's economic status deteriorated and is continuing deteriorating as a result of adverse economic indicators.There ought to be something that has not yet been identified that has led to some Zimbabwean policies being abandoned soon after conception or midway through their life span, while others seem to have achieved less than expected. The findings are critical for the Government of Zimbabwe to advise the stakeholders accordingly on the principal factors that need to be done that will ultimately lead to the attainment of the desired goals. The study recommends areas which might need change management.